2023
DOI: 10.1213/ane.0000000000006369
|View full text |Cite
|
Sign up to set email alerts
|

Performance of the SEDLine Monitor: Age Dependency and Time Delay

Abstract: BACKGROUND: Devices monitoring the hypnotic component of general anesthesia can help to guide anesthetic management. The main purposes of these devices are the titration of anesthesia dose. While anesthesia at low doses can result in awareness with intraoperative memory formation, excessive administration of anesthetics may be associated with an increased risk of postoperative neurocognitive disorder. We have previously shown for various indices that they are significantly influenced by the patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 41 publications
1
11
0
Order By: Relevance
“…In our study, there was a trend that age will increase the PSI number. This aligns with a recent retrospective study finding that the patient’s age significantly influences both PSI and SEF (signal edge frequency) [ 19 ]. Previous studies with the BIS monitor also showed an index increase with age [ 20 ].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In our study, there was a trend that age will increase the PSI number. This aligns with a recent retrospective study finding that the patient’s age significantly influences both PSI and SEF (signal edge frequency) [ 19 ]. Previous studies with the BIS monitor also showed an index increase with age [ 20 ].…”
Section: Discussionsupporting
confidence: 91%
“…The PSI number generation lags behind the real-time tracings displayed on the SedLine ® monitor which are a highly reliable indication of the brain functional state. This delay time by SedLine ® monitor is reported by Obert et al [ 19 ] and is estimated to be more than 50 s. This is longer than qCON and BIS delay that is approximately 25 s [ 21 , 22 ]. Therefore, it is important for the treatment team to be familiar with the interpretation of frontal brain waves in concert with clinical patient assessment during teatment to prevent SedLine ® PSI data misinterpretaion.…”
Section: Discussionmentioning
confidence: 59%
“…Further support for the dependence of their results on the delivery of excessive doses of propofol can be observed in the reported age gap between the groups with high and low Montreal Cognitive Assessment (MoCA) scores-11 years for propofol and only 4 for sevoflurane-as well as the fact that the cognitively healthy group for sevoflurane was 10 years younger than the cognitively healthy group for propofol. The authors do acknowledge that age presents a significant influence on SEF95 3,4 or median frequency (SEF50) 5 ; however, they fail to acknowledge that this may make their results incomparable. So, in summary, the claim of comparing patients "at similar age and depthof-anesthesia" as stated in the discussion cannot be made in our opinion, and hence, the statement about propofol being a better proxy "preoperative low MoCA" may not hold.…”
mentioning
confidence: 90%
“…As outlined in our article, DoA indices like SEF 95 , and bispectral index (BIS), which are largely similar until burst suppression occurs, do not offer a universal solution for monitoring anesthesia depth. 3,4 Nonetheless, currently, using DoA indices provides the most practical strategy for depth comparison between the groups, aligning with everyday clinical practices. 5 Kreuzer et al seem to suggest that, for comparable levels of consciousness, SEF 95 should be higher under propofol than sevoflurane.…”
mentioning
confidence: 99%
“…In addition, there is a time delay in clinically significant index changes from 30 to 60 seconds, depending on the device. 16 Artifact such as muscle activity under the pEEG sensor, and electrocautery can influence index values.…”
Section: Peeg Monitoringmentioning
confidence: 99%